Pengaruh Keahlian Pemakai, Intensitas Pemakaian Dan Penerapan Teknologi Informasi Terhadap Kualitas Informasi Akuntansi Pada Kantor Desa Di Kecamatan Penebel - Wijayanta Putra, Putu Yudha; Samtika Putra, I Putu Deddy; Lesmana Putra, I Made Endra (UNHI Press, 2025)
An important aspect of running a successful business is having the resources to gather accurate information. It is important to have access to current and relevant data for effective and efficient management decision making. This study was carried out to analyze the influence of user knowledge, user intensity, and IT use on the accuracy of financial records maintained by the village office in Penebel District. This survey included Penebel District Village Office personnel from 18 offices. Fifty-four participants were selected using a purposive selection method Data were examined using linear regressions. These studies show that users significantly improve the accuracy of financial reports. The reliability of financial records is not influenced by Penggunaan teknologi informasi. Improving the quality of accounting information is a direct result of the use of accounting information technology. Based on research findings, village officials need to continue to receive job training in the future. Improving the quality of accounting data is an initiative that, among other things, aims to improve results by making better use of existing village institutional resources.